THE CONTRIBUTION OF THE MAIN STEM AND BRANCHES OF THE APPROVED CULTIVAR KM5180 TO THE GROWTH CHARACTERISTICS BY THE EFFECT OF THE NUMBER OF SEEDS PER SQUARE METER - M. F. H. Al-Hassan,; J. W. Mahmood, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field experiment conduct during winter season 2022-2023. This study was aimed to investigate effect number of seeds.m2 to two wheat varieties. The results showed the superiority of  V1 in most main stem growth traits (biological yield, number of ears .In square meters, plant height, spike length, spikelets number / ear and chlorophyll content ( 1.87 t. ha, 20.0 seed. m2 , 113.90 cm , 18.40 cm, 26.37 spikelets/ ear  and 75.92 (SPAD ) respectively. V1 also excelled in all the traits of branch growth ( biological yield, number of peduncles /m2, plant height, spike length and spikelets number / ear, (16.71 tons .Ha-1, 259.17 ear /m2  ,104.57 cm, 16.83 cm and 23.63 spikelets / ear ) respectively . comparative to V2 . for the seeding rates per square meter; S2 produced the highest main stem growth traits of biological yield, plant height and chlorophyll content, (16.71 ton. ha-1 , 103.63 cm and 83.99 SPAD) respectively .in compare to (S1 and S3 seeding rates), even more; S2 produced the highest biological yield in tillers No. (14.56 ton .ha-1) which was significantly  higher than seeding rates ((S1 and S3) ], while S3 produced the highest ears number. (265.00 ear.m2) compared to other seeding rates.